Effect of black corn (Zea mays L.) on adipogenesis, inflammation, oxidative stress and intestinal health in vivo - Verediano, Thaísa Agrizzi (2023)
Black corn (Zea mays L.) is a type of colored corns, which shows different colors depending on its chemical composition. Over the past years, colored corn has been targeted for investigation due its bioactive components. Black corn is a source of anthocyanins, which is a water-soluble pigment responsible to the black-purple color. Anthocyanin is a subclass of flavonoids, and its consumption is associated with health promoting effects. Anthocyanin exerts antioxidant and anti-inflammatory effects, besides to modulate the intestinal function. However, anthocyanin shows a different effect depending on its origin, food matrix, or if it is isolated as an extract. The black corn TO 002 belongs to the Germplasm Activate Bank from Embrapa and showed a promising composition of phenolic compounds and anthocyanin. However, the biological effects of this genotype in vivo have never been tested. Therefore, we hypothesized that the black corn have a health-promoting effect in adipogenesis, inflammation, oxidative stress and on intestinal function. Objectives: To critically review the effects of anthocyanin supplementation on intestinal parameters in animal studies (Paper 1); To evaluate the effects of black corn whole flour associated with a high-fat diet in the adipogenesis, inflammation, oxidative stress and on the modulation of intestinal function (Paper 2 and 3); To investigate the effects of black corn soluble extract on the intestinal functionality, morphology and microbiota in vivo (Paper 4); To analyze the effects of black corn anthocyanin-rich extract on intestinal functionality, morphology and microbiota in vivo (Paper 5). Therefore, the general objective of this work was to investigate the effect of black corn (Zea mays L.) on the adipogenesis, inflammation, oxidative stress and on the intestinal health in animal models. Methods: Paper 1: For the systematic review, articles were reviewed following the PRISMA guidelines. The data search was performed at PubMed, Cochrane and Scopus for experimental studies, which evaluated the supplementation of anthocyanin on intestinal parameters. For the original studies: Paper 2 and 3: thirty adult male C57BL/6 mice were randomly divided into 3 groups (n=10/group): NC: normal control – AIN-93 M diet; HF: high-fat diet; HFC: high-fat diet + black corn whole flour (20%), receiving the diets for 8 weeks. The intestinal function was assessed in the content from cecum at the end of the experiment, and gut microbiota composition was evaluated by 16S ribosomal gene sequencing. Paper 4: The biological experiment was conducted by the intra-amniotic approach (Gallus gallus). For this, the eggs were divided into 4 groups (n= 6 - 10/group): No Injection; 18 MΩ H 2 O Injection; 5% black corn soluble extract (BCSE); 15% BCSE. The intra-amniotic administration was performed at the day 17 of embryonic incubation. Sample collection and evaluation of intestinal functionality, morphology and gut microbiota were performed after the hatching (day 21). Paper 4: The biological experiment was conducted by the intra-amniotic approach (Gallus gallus). For this, the eggs were divided into 4 groups (n= 8/group): No Injection; 18 MΩ H 2 O Injection; 5% black corn anthocyanin-rich extract (BCE); cyanidin-3-glucoside (C3G). The intra-amniotic administration was performed at the day 17 of embryonic incubation. Sample collection and evaluation of intestinal functionality, morphology, and gut microbiota were performed after the hatching (day 21). Results: Paper 1: 27 studies in animal’s models were included in the systematic review. The anthocyanin supplementation promoted an enrichment of Bacteroidetes abundance and a decrease of Firmicutes. Further, it improved short chain fatty acids (SCFA) production, which resulted in a lower pH and intestinal permeability, and an increase of goblet cell (GC), tight junction protein expression, and improvements at the villi morphology. Paper 2 and 3: HFC animals improved the total antioxidant capacity and demonstrated lower adipogenesis by showing a decrease at adipocyte number and length by downregulating sterol regulatory element-binding protein-1c (SREBP-1c) and peroxisome proliferator-activated receptor-γ (PPARγ). The consumption of HFC demonstrated to promote hepatic β-oxidation by downregulating the hepatic gene expression of SREBP-1c and acetyl CoA carboxylase 1. Further, the HFC intake prevented disorder at the intestinal function promoted by a high-fat diet. Animals fed a HFC diet had higher abundance of the genus Ruminococcus, Roseburia, and Provotellacea_UCG-001, and lower abundance of the genus Bacteroides and Faecalibaculum. These changes were observed with no changes at SCFA concentration, and with an increase at goblet cell (GC) proliferation. Paper 4: The intra- amniotic administration of BCSE (5 and 15%) demonstrated an anti-inflammatory effect by downregulating the gene expression of duodenal inflammatory biomarker: tumor necrosis factor-alpha (TNF-α), interleukin 6 (IL6), and the transcriptional nuclear factor kappa beta (NF- κB). Further, the BCSE increased the relative abundance of cecal E. coli and Clostridium and improved the duodenal morphology by increasing GC number and size and Paneth cell number. Further, the BCSE demonstrated potential to improve the physical barrier integrity by upregulating the gene expression of AMP- activated protein kinase (AMPK) and caudal-related homeobox transcriptional factor 2 (CDX2). Paper 5: The intra-amniotic administration of BCE demonstrated to increase the relative abundance of the genus Bifidobacterium and Clostridium and to decreased E coli abundance. The BCE maintained biomarkers of intestinal inflammation and functionality similar to the control group. Further, the duodenal morphology was maintained similar to the control after the intra-amniotic administration of BCE. General Conclusion: The black corn demonstrated to exert a beneficial effect in vivo, by acting as an anti-inflammatory and antioxidant component, and by modulating the intestinal function. Thus, the black corn should be considered as a potential source of anthocyanin and phenolic components with proved beneficial effect. Keywords: Anthocyanin. High-fat. Intestinal microbioma. Soluble extract. Whole flour. Anthocyanin rich-extract